IMPLEMENTATION OF PROFILE MATCHING METHOD FOR THE BEST EMPLOYEE SELECTION SYSTEM PT. JENDELA DIGITAL INDONESIA - Prabowo, Donni (LPPM Universitas Nusa Mandiri, 2022)
The implementation of profile matching method in selecting the best employees at PT Jendela Digital Indonesia aims to assist managers in making decisions with the right calculations and criteria. Employees are one of the factors that play an important role in advancing the company. Employee performance affects the company in obtaining profits. To spur employee performance, the company selects the best employees every period by giving appreciation and bonuses to selected employees. This selection system using three criteria, namely aspects of cooperation, work performance, and personality. These criteria will be used for calculations using the Profile Matching method. There are five employees who will be submitted to the selection of the best employees in this company. All criteria are given a GAP value and then will provide a ranking. The largest final score will be at the top of the ranking, followed by a smaller final score. The results of this research show that this method can provide results that assist managers in making decisions about the best employees according to the criteria desired by the company.